Organizational socialization: does it effects second career success of practitioners-turned academics - Mohd Rasdi, Roziah; Mohd Pauzi, Khairunnisa (2016)
The purpose of the study was to investigate the effect of organizational socialization as a mediating variable between individual-related factors (self-efficacy, proactive career, extraversion and conscientiousness) and second career success (i.e, objective career success, subjective career success, and academic performance). The sample of this study consisted of practitioners-turned-academics from various universities in Malaysia. Data were gathered from 175 practitioners-turned-academics using self-administered questionnaires. Structural equation modelling was employed to testing the mediation effects. Results indicated that organizational socialization did not mediate the relationship between the individual-related factors and second career success. Implication and recommendation for future research are put forth.